A systematic review of quantitative studies capturing measures of psychological and mental health for Gay and Lesbian individuals of faith - Wilkinson, Dean J. (Mental health, religion & culture, 2021)
The association between religion or spirituality and psychological concepts (e.g., subjective well-being), have received frequent support, however, recent evidence has noted that cultural factors may affect this relationship. The consideration of these concepts for sexual orientation minorities has been neglected in previous years and now a body of evidence is beginning to develop around concerns for this population, with some speculation for the changes of ‘stressors' for future generations and the implication on mental health outcomes. Lesbian and Gay individuals of faith (or spirituality), are susceptible to unique ‘stressors’, whilst others suggest religion can provide a support network providing protective health benefits. This review explores the evidence for psychological measures associated with LGB people of faith. The evidence suggests following a religion or faith can provide good social support, reducing health risks, however, can have negative implications for mental and physical health such as, internalised homophobia, anxiety and rejection.